2021
DOI: 10.3390/molecules26072029
|View full text |Cite
|
Sign up to set email alerts
|

The Hallmarks of Flavonoids in Cancer

Abstract: Flavonoids represent an important group of bioactive compounds derived from plant-based foods and beverages with known biological activity in cells. From the modulation of inflammation to the inhibition of cell proliferation, flavonoids have been described as important therapeutic adjuvants against several diseases, including diabetes, arteriosclerosis, neurological disorders, and cancer. Cancer is a complex and multifactor disease that has been studied for years however, its prevention is still one of the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 364 publications
(235 reference statements)
3
85
0
Order By: Relevance
“…Consumption of flavonoids is reported to induce apoptosis in GI cancer, acting as a potential therapeutic agent [147]. Flavonoids could induce apoptosis by acting on the intrinsic apoptotic pathway, as in the case of fisetin.…”
Section: Effects Of Flavonoids On Gastrointestinal Cancermentioning
confidence: 99%
“…Consumption of flavonoids is reported to induce apoptosis in GI cancer, acting as a potential therapeutic agent [147]. Flavonoids could induce apoptosis by acting on the intrinsic apoptotic pathway, as in the case of fisetin.…”
Section: Effects Of Flavonoids On Gastrointestinal Cancermentioning
confidence: 99%
“…Various studies reported that API, OA, BA, and BS administration inhibits NF-κB (IkBa) kinase (IKKß) and phosphorylation of IkBa, which leads to the suppression of NF-κB activation [ 14 , 20 , 22 , 23 , 24 ]. TNFR activation by TNF-α is also important for TAK1 activation, and consequently, activation of NF-κB signaling [ 6 ]. It is perceived that Th-1 derived cytokines such as IL-2, IFN-γ, and IL-12 improve cellular immunity, whereas Th-2 derived cytokines such as IL-4, IL-5, IL-6 employ negative immunoregulatory effects on cellular immunity.…”
Section: Inflammation and Immunitymentioning
confidence: 99%
“…M1 and M2 cells have diverse chemokine and chemokine receptor repertoires and thus orchestrate different immune responses. It is seen that QU and API may indirectly prevent inflammation by affecting peroxisome proliferator-activated receptor gamma (PPARγ) activity, antagonizing the NF-κB pathway or Activator protein 1 (AP-1) transcriptional activation of inflammatory genes, thereby reducing inflammation by successfully differentiating infiltrating macrophages to an anti-inflammatory M2 phenotype [ 6 , 9 , 27 ].…”
Section: Inflammation and Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The acylated flavonoids are mainly with hydroxycinnamic acids (HCA), particularly coumaric, caffeic, sinapic and ferulic acids (Olsen et al, 2009;Sun et al, 2013). Recent review papers have compiled numerous studies pointing towards the neuroprotective and anti-carcinogenic effects of flavonoids, suggesting a diet containing these compounds may be part of the treatment for Alzheimer's disease and several cancers (Kim and Park, 2021;Ponte et al, 2021).…”
Section: Introductionmentioning
confidence: 99%